Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26 - 29, 2023, Los Angeles, California, - Rathje, Ellen M.; Montoya, Brina; Wayne, Mark H. (GSP (Series) ;, 2023)
The fourth volume of six Geotechnical Special Publications (GSPs) contains 63 peer-reviewed papers presented at Geo-Congress 2023 on foundation engineering, earth retention, and geosynthetics. Topics include: deep and shallow foundations; earth retaining structures; and use of geosynthetics in geotechnical systems.